2021
DOI: 10.1002/jmv.26741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum IgM and IgG antibodies in COVID‐19 patients by enzyme linked immunosorbent assay

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is sweeping the world since the end of 2019. The titer change of antibodies against SARS-CoV-2 needs to be further clarified, the clinical and preventive value of antibodies still needs to be further investigated. An enzyme-linked immunosorbent assay (ELISA) was established by coating with SARS-CoV-2 recombinant spike protein and used to detect serum immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies against SARS-CoV-2 in coronavirus diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…1 Humoral immune response (IgG, IgM, IgA) profiles of SARS-CoV-2 infections: onset and persistence of neutralising antibodies. a Onset within 10–14 days [ 27 32 ]; levels remain elevated for weeks [ 30 , 33 38 ]; peaks at around day 25 [ 26 ]. b Rises within the first week of infection [ 30 , 31 , 33 , 39 ]; lasts 1-2 months before gradually diminishing [ 15 , 30 , 38 ]; peaks at around 20–30 days post-symptom onset [ 40 ].…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Humoral immune response (IgG, IgM, IgA) profiles of SARS-CoV-2 infections: onset and persistence of neutralising antibodies. a Onset within 10–14 days [ 27 32 ]; levels remain elevated for weeks [ 30 , 33 38 ]; peaks at around day 25 [ 26 ]. b Rises within the first week of infection [ 30 , 31 , 33 , 39 ]; lasts 1-2 months before gradually diminishing [ 15 , 30 , 38 ]; peaks at around 20–30 days post-symptom onset [ 40 ].…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
“…a Onset within 10–14 days [ 27 32 ]; levels remain elevated for weeks [ 30 , 33 38 ]; peaks at around day 25 [ 26 ]. b Rises within the first week of infection [ 30 , 31 , 33 , 39 ]; lasts 1-2 months before gradually diminishing [ 15 , 30 , 38 ]; peaks at around 20–30 days post-symptom onset [ 40 ]. c Onset within 6–8 days [ 39 ]; lasts 71 days [ 38 ]; peaks at around 20–22 days post-symptom onset [ 39 , 40 ]; high titres in severe COVID-19 cases [ 32 ] …”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 274 cases of contact history 80 (29.19%) were reactive and out of 169 with travel history 28 (16.5%) were reactive cases. Analysis of a study found that close contacts to confirm COVID-19 cases revealed a relatively short infectious period of COVID-19 and a higher transmission risk around the time of symptom onset of the index case, followed by a lower transmission risk at the later stage of disease [18]. Age difference in reactive and non-reactive subjects was non-significant in the study.…”
Section: Discussionmentioning
confidence: 61%